Using Murine Models to Investigate Tumor–Lymphoid Interactions: Spotlight on Chronic Lymphocytic Leukemia and Angioimmunoblastic T-Cell Lymphoma - Herek, Tyler A.; Cutucache, Christine E. (Frontiers in Oncology, 2017)
The role of the tumor microenvironment in leukemias and lymphomas is well-established, yet the intricacies of how the malignant cells regulate and influence their non-malignant counterparts remain elusive. For example, chronic lymphocytic leukemia is an expansion of malignant CD5+CD19+ B cells, yet the non-malignant T cells play just as large of a role in disease presentation and etiology. Herein, we review the dynamic tumor cell to lymphoid repertoire interactions found in two Non-Hodgkin’s lymphoma subtypes: chronic lymphocytic leukemia and angioimmunoblastic T-cell lymphoma. We aim to highlight the pivot work done in the murine models which recapitulate these diseases and explore the insights that can be gained from studying the immuno-oncological regulation of non-malignant lymphoid counterparts.